A General Amalgamate Technique to Evaluate Human Health Risk Under Uncertain Circumstances. (September 2022) - Dutta, Palash; Akhtari, Sayesta
Evaluation of humans' health risk is an essential and most demanding aid in relevance to the process of decision-making. Accumulation of quality knowledge on the attributes of each and every available data, information and model parameters, involved in risk assessment, plays a crucial role in the process of evaluation. It is important to note that, most frequently, model parameters are imprecise due to the availability of limited data and knowledge. Under such circumstances, probability theory (PT) and the theory of fuzzy sets can be brought forth to deal with the emerging uncertainties. There is also a need to devise an amalgamate technique to perform health risk assessment under uncertainty. Although some different approaches are available in this regard, all approaches are situation or problem dependent and fail to address some specific issues. Therefore, this article presents a general amalgamate technique to address all the concerned issues, and, finally, health risk is carried out using this approach.